2022
DOI: 10.1186/s13062-022-00347-5
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine-mediated SH3BP5-AS1 upregulation promotes GEM chemoresistance in pancreatic cancer by activating the Wnt signaling pathway

Abstract: Background Pancreatic cancer (PC) is highly malignant. Chemotherapy is the main treatment strategy, especially for patients with advanced PC. However, chemoresistance has always been a frequently encountered bottleneck. Hence, there is an urgent need to enhance the sensitivity of PC to gemcitabine (GEM). Results We demonstrated that SH3BP5-AS1 was significantly upregulated in GEM-resistant PC and predicted a poorer prognosis. SH3BP5-AS1 stability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 42 Dysregulation of m6A also contributes to the development of gemcitabine resistance. 43 Moreover, the effect of DAPK3 on chemotherapy resistance has been well established in previous studies, which induces the loss of cell‐to‐cell adhesion, thereby conferring more sensitivity to chemotherapy. 26 , 27 Consistent with this evidence, we observed that YTHDF2 mediated resistance to gemcitabine in GBC cells through DAPK3.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 42 Dysregulation of m6A also contributes to the development of gemcitabine resistance. 43 Moreover, the effect of DAPK3 on chemotherapy resistance has been well established in previous studies, which induces the loss of cell‐to‐cell adhesion, thereby conferring more sensitivity to chemotherapy. 26 , 27 Consistent with this evidence, we observed that YTHDF2 mediated resistance to gemcitabine in GBC cells through DAPK3.…”
Section: Discussionmentioning
confidence: 94%
“…In ovarian cancer, Nicotinamide N‐methyltransferase (NNMT) mRNA is demethylated and upregulated by Fat mass and obesity‐associated protein (FTO), thereby increasing sensitivity to platinum 42 . Dysregulation of m6A also contributes to the development of gemcitabine resistance 43 . Moreover, the effect of DAPK3 on chemotherapy resistance has been well established in previous studies, which induces the loss of cell‐to‐cell adhesion, thereby conferring more sensitivity to chemotherapy 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lin illustrated that lncRNA SH3BP5‐AS1 was significantly upregulated in gemcitabine‐resistant pancreatic cancer cells and this upregulation was found to be associated with a poor prognosis for PC patients. Mechanistically, the stability of SH3BP5‐AS1 was negatively regulated by ALKBH5/IGF2BP1‐mediated m6A modification 131 . Furthermore, increased m6A‐modified lncRNA DBH‐AS1 suppressed GEM resistance in pancreatic cancer.…”
Section: Interaction Between M6a Modification and Lncrna In Cancer Dr...mentioning
confidence: 99%
“…Mechanistically, the stability of SH3BP5‐AS1 was negatively regulated by ALKBH5/IGF2BP1‐mediated m6A modification. 131 Furthermore, increased m6A‐modified lncRNA DBH‐AS1 suppressed GEM resistance in pancreatic cancer. DBH‐AS1 increased sensitivity of PC cells to GEM by sponging miR‐3163 and upregulating USP44 in PC cells.…”
Section: Interaction Between M6a Modification and Lncrna In Cancer Dr...mentioning
confidence: 99%
“…A handful of lncRNAs have been discovered to modulate m 6 A writers as well. The lncRNA UCA1, for example, accelerates the course of acute myeloid leukemia by connecting to METTL14 to elevate m6A quantities and augment CXCR4 and CYP1B1 expression ( Li et al, 2022a ). Nevertheless, the modulation of m 6 A erasers associated with lncRNAs has only occasionally been documented, which could offer fresh perspectives on the course of future research and open up opportunities for the treatment of cancer.…”
Section: Roles Of Non-coding Rnas On M 6 a Regulat...mentioning
confidence: 99%